PEREMPUAN DALAM BUDAYA PATRIARKI: KAJIAN SEMIOTIKA SOSIAL DALAM CERPEN SUNDA BERJUDUL “SI BOCOKOK” - Heni Haryani (UNIVERSITAS KEBANGSAAN, 2020)
Abstract. This study analyzes how the position of women in household life in patriarchal culture in Sundanese society which was also described in a short story entitled